Upstream supply chain vulnerability, robustness and resilience : a systematic review of literature - Tewari, Anurag (Cranfield University, 2013)
Purpose: In the last decade, supply chains of many global firms have been exposed to severe and costly supply chain disruptions. Triggered by either a manmade or a natural disaster, these disruptions are often a result of the increased network complexity and interdependency. One of the many contributing factors to this increased network complexity is the conscious effort by organizations to over optimise their efficiency and performance. The field of supply chain resilience, robustness and vulnerability studies, a new and growing area of knowledge, is contributing towards discovering the causes leading to supply chain disasters and measures to tackle them. Criticized to be highly fragmented and fraught with conceptual ambiguity, the filed has been evolving by incorporating vulnerability and resilience research from other interdisciplinary domains. This present research aims at mapping the intellectual territory of the resilience, robustness and vulnerability domain by conducting a literature review. The review also aims to establish a conceptual clarity in the definition of terms and constructs relevant to the field and to discover conceptual and methodological gaps in the existing body of literature. Design/methodology/approach: This literature review is conducted using a systematic review approach which benefits from a clearly defined audit and decision trail. After filtering through 2077 titles, the review is taken up for 43 articles. Findings: The review demonstrates that the drivers of vulnerability and strategies to tackle it can be grouped into three themes, Structural, Operational and Strategic. The review also demonstrates that the field is still plagued with conceptual ambiguity. By the analysis of the findings, a number of research directions were identified. Research limitations/implications: Major limitations to this study were the associated personal bias in quality assessment of included and excluded articles. Also, due to blurred definitions of terms and constructs in the literature, the thematic classification of findings could be challenged. Lastly, it cannot be stated with conviction that the chosen 43 articles are sufficient. Practical implications: This research highlights the future conceptual and methodological prospects in the field of resilience, robustness and vulnerability. The direction of structural research proposed in the thesis has a very high potential to secure future supply chains. Originality/value: This review is first to address the issue of SCV, SCRel and SCRob. The review provides an extensive overview of the present extant of the vulnerability, robustness research and it proposes a thematic framework to further extend the knowledge in this filed.
Keywords: Supply Chain; Robustness; Reliability; Risk Mitigation; Upstream; Network